Influence of method and date of planting on the production of lettuce (Bangladesh Journal of Agricultural Research, 2010)
The effect of two planting methods (direct seed sowing and transplanting of seedlings) and seven dates of planting (8 Oct., 2 Nov., 27 Nov., 22 Dec., 16 Jan., 10 Feb. and 5 March) on the production of lettuce was compared. ‘Green Wave’ a loose leaf Japanese variety was used. The average yield of the direct seeded crops (17.16 t/ha) was found to be almost double than that of the transplanted crops (9.08). The yields (t/ha) from different dates of planting were 13.7 (8 Oct.), 15.04 (2 Nov.), 8.94 (27 Nov.), 14.54 (22 Dec.), 21.45 ( 16 Jan.) 10.16 (10 Feb.), and 8.02 (5 March). The highest yield of 24.0 t/ha was obtained from direct seedling on 16 January. Key Words: Method; date; planting; production of lettuce. DOI: 10.3329/bjar.v34i1.5756Bangladesh J. Agril. Res. 34(1) : 75-80, March 2009